Length-weight relationship and condition factor of Schilbe mystus in Dadin kowa reservoir - Hassan S. K.,; Umar, D.M,; Saidu H.,; Khadija, A., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
A study on length-weight relationship and condition factor of Schilbe mystus in Dadin Kowa Reservoir was carried for a period of three months. The results obtained showed that the growth pattern of the fishes were negatively allometry (when b<3 i.e the fish grows faster in length than in weight) with b values of 2.5 obtained at P<0.001. There was perfect correlation between the length and weight of all the species. The condition factor was 0.8, an indication that the fish were thriving well in the reservoir. The length-weight relationship and condition factor determined from this study indicated the productivity level of the researvoir for sustainable fish conservation.